New Plasmodium vivax Genomes From the China-Myanmar Border - Brashear, Awtum M.; Huckaby, Adam C.; Fan, Qi; Dillard, Luke J.; Hu, Yubing; Li, Yuling; Zhao, Yan; Wang, Zenglei; Cao, Yaming; Miao, Jun; Guler, Jennifer L.; Cui, Liwang (Frontiers in Microbiology, 2020)
Plasmodium vivax is increasingly the dominant species of malaria in the Greater Mekong Subregion (GMS), which is pursuing regional malaria elimination. P. vivax lineages in the GMS are poorly characterized. Currently, P. vivax reference genomes are scarce due to difficulties in culturing the parasite and lack of high-quality samples. In addition, P. vivax is incredibly diverse, necessitating the procurement of reference genomes from different geographical regions. Here we present four new P. vivax draft genomes assembled de novo from clinical samples collected in the China-Myanmar border area. We demonstrate comparable length and content to existing genomes, with the majority of structural variation occurring around subtelomeric regions and exported proteins, which we corroborated with detection of large-scale copy number variation. We predicted peptides from all PIR gene subfamilies, except for PIR D. We confirmed that proteins classically labelled as PIR D family members are not identifiably by PIR motifs, and actually bear stronger resemblance to DUF (domain of unknown function) family DUF3671, potentially pointing to a new, closely related genetic family. Further, phylogenetic analyses of MSP7 genes showed high variability within the MSP7-B family compared to MSP7-A and -C families, and the result was comparable to that from whole genome analyses. The new genome assemblies serve as a resource for studying P. vivax within the GMS.